1997
DOI: 10.1007/s001060050113
|View full text |Cite
|
Sign up to set email alerts
|

Die Pegelzunahme von Distorsionsproduktemissionen des Menschen durch kontralaterale Beschallung niedriger Intensität

Abstract: Distortion product otoacoustic emissions (DPOAEs) are probably based on the motile properties of the cochlear outer hair cells (OHCs), which are richly innervated by medial olivo-cochlear efferent nerves (MOCs). DPOAEs provide a stimulating model for functional exploration of the efferent system. The influences of contralateral acoustic stimulation were studied on the amplitude of ipsilateral DPOAEs at the frequency 2f1-f2. Fifteen ears of adults with normal hearing (7 women, 8 men, mean age; 23.1 +/- 4.2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Similar ndings have previously been reported in both humans (12,17,18) and animals (22). Thus, the efferent bers do not necessarily have to have a suppressive in uence on OHC motility.…”
Section: Comparison Of Changes With Different Spectrasupporting
confidence: 83%
See 2 more Smart Citations
“…Similar ndings have previously been reported in both humans (12,17,18) and animals (22). Thus, the efferent bers do not necessarily have to have a suppressive in uence on OHC motility.…”
Section: Comparison Of Changes With Different Spectrasupporting
confidence: 83%
“…Moreover, some studies in humans have also demonstrated an enhancement of SOAE (8), DPOAE (12,17) and TEOAE (18) amplitudes in the presence of CS. Nieschalk et al (17) observed that contralateral pure tones at frequencies \750 Hz and with intensities of 30 dB HL increased DPOAE amplitudes. The mechanisms of both the enhancement and suppression effects remain unclear.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 12 of these, stimulus frequency was varied whereas primary tone levels were held constant (Bassim et al, 2003;James et al, 2002;Kim et al, 2002;Lisowska et al, 2002;Di Girolamo et al, 2001;Sasaki et al, 2000;Timpe-Syverson and Decker, 1999;Williams and Brown, 1995;Moulin et al, 1992;Nieschalk et al, 1997;Chery-Croze et al, 1993;Moulin and Carrier, 1998). Reported suppression effects ranged from <1 to a few dB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the term DPOAE suppression is misleading because it was found that not only suppression but also enhancement of the DPOAE amplitude occurs (e.g. Nieschalk et al, 1997;Kujawa and Liberman, 2001). Therefore, in the following this technique is referred to as CAS DPOAE.…”
Section: Introductionmentioning
confidence: 94%